GAME PETUALANGAN WARAK NGENDOG SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA SD MENGGUNAKAN ALGORITMA COLLISION DETECTION BERBASIS ANDROID - Ryan Ramawan, Dicky; Eniyati, Sri (Information Technology and Telematics, 2018)
ABSTRACT Warak Ngendog is a typical Semarang city toy that appears once and is only present at the Dugderan tradition celebration. His head resembled a dragon's head (Chinese), his body was like a buraq (Arabic), and his four legs resembled a goat's feet (Javanese). Today's technological developments make people, especially children, who are lazy to learn and choose to play games through smartphones. The concept of the game "The Adventure of Warak Ngendog" that will be made by the author is an educational game and mathematics learning for elementary school students in grade 1 who are expected to increase learning interest. The method of making this game is coillision detection. The game model is presented in the form of warak ngendog as the main character, and there are 3 levels of adventure genre. Level 1 is a multiple choice quiz question, level 2 in the form of picture guessing and level 3 in the form of a puzzle game. Tests are carried out using 3 different Android devices. The results showed that the game "Adventure of Warak Ngendog" made using construct 2 can be run on a mobile device with an android platform.